Analisis Uji Emisi Pada Asap Hasil Pembakaran Briket dari Campuran Batubara dan Limbah Plastik LDPE: Emission Test Analysis On Bricket Combustion Smoke From Mixed Coal And LDPE Plastic Waste - Asmiani, Nur; Lestari, Ayu; Thamsi, Alam Budiman (CV Insight Publisher, 2024)
This research was conducted by mixing coal and Low-Density Polyethylene (LDPE) waste. This study aimed to determine the smoke resulting from burning briquettes with a calorific value of 9,187 Kcal/gr. Judging from the emission levels of carbon monoxide (CO), sulfur dioxide (SO2), and nitrogen oxides (NO2), it becomes a consideration for the feasibility of briquettes be produced as alternative fuels, harmful or not for human health and the surrounding environment. They are first testing the quality of the briquettes and the smoke emissions from burning briquettes. From the test results, the sulfur content is 0.01%, the moisture content is 1.15%, the ash content is 10.22%, the volatile matters are 87.76%, and the calories are 9187.64 Kcal/gr. Then the smoke resulting from burning briquettes was tested for emission levels of carbon monoxide (CO), sulfur dioxide (SO2), and nitrogen oxides (NO2). The results obtained with a high value and exceed the maximum standard that has been set by PERMEN ESDM No. 047 of 2006, namely CO 13715 mg/Nm3 and SO 2550 mg/Nm3, while the NO 2 produced does not exceed the maximum standard set by PERMEN ESDM No. 047 of 2006 which is 7 mg/Nm3. Based on the test results, it can be concluded that the briquettes produced have the potential to pollute the environment and are dangerous if inhaled at high levels by humans. The resulting briquettes are also unfit to be produced as an alternative fuel.